Pengaruh Fraksi Volume dan Waktu Perendaman Serat Rami Terhadap Kekuatan Impak Sebagai Alternatif Material Skateboard - Fina Andika Frida Astuti; Achmad Ali Ridho; Arif Rochman Fachrudin (Infotekmesin, 2026)
Skateboards are typically made from maple wood, which is strong and flexible; however, its availability is not always guaranteed in terms of quantity or quality. One potential solution is the use of natural fiber-based composite materials, particularly ramie fiber, which is known to have higher impact strength than other natural fibers, making it suitable for skateboard applications that require high impact resistance. This study examines the effect of varying fiber volume fractions (25%, 45%, and 65%) and soaking durations in a 5% NaOH solution (2 hours, 3 hours, and 4 hours) on the impact strength of epoxy-matrix composites. Specimens were fabricated using the hand lay-up method and tested using the Charpy impact method in accordance with ASTM E23. Test results showed that the highest impact strength was obtained at a 65% volume fraction with a 3-hour immersion duration, at 0.08555 J/mm², while the lowest impact strength occurred at a 25% volume fraction with a 4-hour immersion duration, at 0.02823 J/mm². These results indicate that ramie fiber composites have the potential to be developed as a lighter and more environmentally friendly alternative material for skateboards.